Nominal Forms of Address Used by Young People in Medellin When Addressing their Significant Others - Castellano Ascencio, Milton Daniel (Íkala, Revista de Lenguaje y Cultura, 2008)
This article presents a lexical-pragmatic description of nominal forms of address (NFA) used by young people in Medellin when addressing their significant other. To this aim, studies issued in Spanish concerning NFA were reviewed, as well as some fundamental concepts on NFA. The tokens of NFA from the corpus considered for analysis were classified according to the semantic-pragmatic values affecting their meaning. A particular analysis of some of these tokens is presented. The article also remarks on the function of contextual factors involved in the interpretation of NFA. Received: 30-03-2008 / Accepted: 25-07-2008 How to reference this article: Castellano Ascencio, M. D. (2008). Fórmulas de tratamiento nominales para la pareja en el habla juvenil medellinense. Íkala. 13(2), pp.163-181.